Halkevi Libraries, as a Unique Library Model within the Context of the Republic's Regime - Altay, Ahmet; Yılmaz, Bülent; Altay, Ahmet (Turkish Librarians Assoc, 2024)
Purpose: The present study examines the library services of halkevleri (community centres), one of the most important cultural organisations of the founding period of the Republic of T & uuml;rkiye. The study presents a series of examples of various activities and services carried out in halkevi libraries. The number of studies on halkevi libraries in the field of information and records management in T & uuml;rkiye is quite limited. In this context, the study aims to fill the gap in the Turkish literature on this subject. Method: This study utilised the documentary review method, one of the qualitative research methods. The documentary review method involves finding, reading, transcribing, and appraising sources within the framework of a specific purpose. In this scope, the current study analysed the publications related to the services of the halkevleri, halkevi journals, periodicals of the period, archival records, and sources written on the subject of halkevleri. Findings: The findings of the study revealed significant information regarding the structuring of halkevi libraries, working hours, technical and user services, collection development policies, selection and acquisition processes, lending procedures, local characteristics, publishing activities, public relations studies, and the use of technology. In addition, the study also includes valuable information about special research libraries, prison libraries, childrens' libraries, and mobile libraries established by the halkevi libraries. Moreover, it presents various examples of creative activities and practices conducted in halkevi libraries. Implications: The information and findings obtained in the study concluded that the halkevi libraries of the period have a number of characteristics that an ideal public library is expected to have in the present conditions such as locality, user-centricity, creativity, innovation, flexibility, participation, and governance. In this context, Halkevi libraries are organisations that serve as an example and a guide even for present-day public libraries considering the services they provide and the vision they have. Originality: The information and findings were obtained from primary sources such as archival sources and halkevi journals. The majority of the findings used in the study were not encountered in previous scientific studies on this subject. In this respect, the findings of the study are considered to be original and to contribute to the field of information and records management.
Cumhuriyet Tarihinin Özgün Kütüphane Modeli Olarak Halkevi Kütüphaneleri
Keywords: Halkevi; Halkodas & Imath; Halkevi Libraries; Public Library Services; T & Uuml; Rkiye